An opening : twelve love stories about art - Radok, Stephanie (Kent Town, S. Aust. : Wakefield Press, 2012)
"Stephanie Radok engages sensuously and poetically with the art she has seen from her place in the suburbs of Adelaide and as a citizen of the world. Her contribution to Australian art is idiosyncratic and determinedly marginal." -- Cover.
Includes bibliography (p. 161-168).
Keywords: Art in literature; Yolngu people (NT SD53); Art - Painting; History - Biographies - Indigenous; Art - Painting - Bark; Death - Mortuary / funeral ceremonies - Mortuary objects - Poles; Art - Theory and criticism; Race relations - Racism; Art - Artists - Non-Indigenous.; History - Biographies - Non-Indigenous.; Art - Artists; Culture - Relationship to place; Malanbarra / Gulngay people (Y126) (Qld SE55-06); Religion - Dreaming; Adelaide (SE SA SI54-09); Canberra (ACT SI55-16); Pukatja / Ernabella (SA Central Australia SG53-09); Angurugu (Groote Eylandt NT Gulf Islands SD53-07); Glyde River (Central Arnhem Land SD53-02); Papunya (South Central NT SF52-16); Warmun / Turkey Creek (WA East Kimberley SE52-06); Australian